Effects of calcium, sodium and potassium on ash fusion temperatures of solid recovered fuels (SRF). (1st August 2022) - Szydełko, Arkadiusz; Ferens, Wiesław; Rybak, Wiesław
Highlights: SRF composition influences on melting characteristic of ashes. Slag viscosity index Sr forecasts the influence of ash oxide composition on melting. High concentration of calcium compounds counteracts the ash melting point reduction. High concentration of calcium compounds prevents the melt phase formation. The ashes of SRF rich in waste paper (CaCO3 ) has high values of the melting point. Abstract: Various types of solid recovered fuels (SRFs) were investigated, then the waste was chemically leached and co-fired with coal and sewage sludge. Ashes with different properties and oxide compositions were used to explain the influence of various ash components (mainly sodium, potassium and calcium) on the Ash Fusion Temperatures (AFTs). Oxide compositions and empirical indices were determined and the effect of these data on the measured AFTs was investigated. An attempt to explain the effects of specific oxides on SRF melting temperatures using FactSage thermodynamic equilibrium software is presented. Thermodynamic equilibrium calculations are also used to predict the onset temperature of the molten phase, the percentage of molten phase at different combustion temperatures, and the possible solid phases that may exist at different temperatures. The mechanism of transformation of the inorganic substance of SRF turned out to be more complex than that of the mineral substance of coal, which resulted from the variable composition of the SRF. The character of temperature changes of the studied wastes after leaching in water and acetic acid in most cases is similar to the courses determined experimentally. For all investigated ashes from obtained the leaching of SRF wastes, the melting temperature decreases with the applied leaching. Potassium and sodium are the key elements causig the formation of low-melting silicates. Depending on the type of waste and leaching agent the lower the value of the B/A and α indices and the CaO content in ash, the lower the shrinkage temperature of the ash.